Divergent professionalizations in the Argentine federal police and security forces - Constanstino, Gabriel (Universidad Nacional del Litoral, 2021)
The objective of our work is to survey and analyze the perceptions of officers and subordinates about the professional competencies required and the ways to acquire them in the four federal police and security forces in Argentina. To this end, we prepared a descriptive study based on secondary sources and interviews with members of the forces that inquire about these issues. The results of this work contribute to the development of education and training devices that are sensitive to the particular demands of police professionalization in the preventive and investigative groups of the federal forces.